Open government, emerging technologies and public information - STRINGHINI, Antonella (Revue internationale des Gouvernements Ouverts, 2020)
On an international level, countries face major problems of citizen distrust towards State institutions, episodes of corruption, lack of legitimacy in public decisions and discredited public organizations. Faced with this scenario, initiatives were taken to promote State openness and transparency. In 2011, the Open Government Partnership (hereinafter OGP) was launched worldwide, aimed towards fostering concrete commitments from governments to promote transparency, increase citizen participation in the debate and decision making process of public affairs, combat corruption and take advantage of new technologies to strengthen democratic governance and the quality of public services. In 2015, the United Nations General Assembly adopted the 2030 Agenda for Sustainable Development1, where it established 17 Sustainable Development Goals (hereinafter SDGs) to achieve in the next 15 years. SDG No. 16 refers to promoting peaceful and inclusive societies for sustainable development, facilitating access to justice for all and building effective and inclusive institutions at all levels. Among the goals to achieve this SDG are the following: creation of effective and transparent institutions that are accountable at all levels; ensuring the adoption of inclusive, participatory and representative decisions at all levels, and able to meet the required needs; and guarantee public access to information and protect fundamental freedoms, in accordance with national laws and international agreements.